2017
DOI: 10.1007/s10549-017-4518-8
|View full text |Cite
|
Sign up to set email alerts
|

Ribociclib plus letrozole versus letrozole alone in patients with de novo HR+, HER2− advanced breast cancer in the randomized MONALEESA-2 trial

Abstract: PurposeDetermine the efficacy and safety of first-line ribociclib plus letrozole in patients with de novo advanced breast cancer.MethodsPostmenopausal women with HR+ , HER2− advanced breast cancer and no prior systemic therapy for advanced disease were enrolled in the Phase III MONALEESA-2 trial (NCT01958021). Patients were randomized to ribociclib (600 mg/day; 3 weeks-on/1 week-off) plus letrozole (2.5 mg/day; continuous) or placebo plus letrozole until disease progression, unacceptable toxicity, death, or tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 25 publications
5
78
0
6
Order By: Relevance
“…Comparable efficacy has also been demonstrated in the sub‐group with de novo advanced breast cancer in the MONALEESA‐2 study. The median PFS was not reached in the ribociclib plus letrozole arm compared with 16.4 months with letrozole (HR 0.45; 95% CI 0.27 to 0.75) . In addition, ribociclib plus a NSAI also had clinical activity in patients with high burden of disease, and was associated with a lower rate of treatment discontinuation in patients with three or more metastatic sites compared to placebo (45% vs. 60%) …”
Section: Clinical Trial Data: Efficacymentioning
confidence: 97%
“…Comparable efficacy has also been demonstrated in the sub‐group with de novo advanced breast cancer in the MONALEESA‐2 study. The median PFS was not reached in the ribociclib plus letrozole arm compared with 16.4 months with letrozole (HR 0.45; 95% CI 0.27 to 0.75) . In addition, ribociclib plus a NSAI also had clinical activity in patients with high burden of disease, and was associated with a lower rate of treatment discontinuation in patients with three or more metastatic sites compared to placebo (45% vs. 60%) …”
Section: Clinical Trial Data: Efficacymentioning
confidence: 97%
“…Following the results of PALOMA-1, 30 PALOMA-2 31 and PALOMA-3, 32 palbociclib was approved by FDA in the United States and EMA in Europe for the treatment of patients with metastatic BC ER-positive HER2-negative in combination with AIs or fulvestrant. Ribociclib has been approved by the FDA and EMA for the same indications as palbociclib, based on the results of MONALEESA-2, 33 MONALEESA-3 34 and MONALEESA-7. 35 The Phase 3 MONARCH study demonstrated the clinical efficacy and safety of abemaciclib, achieving similar results in combination with AIs and fulvestrant.…”
Section: Er+ Advanced Bc Clinical Data Of Cdk 4/6 Inhibitors In Advanmentioning
confidence: 99%
“…Palbociclib was tested in combination with letrozole 2.5 mg/day in the PALOMA-1 and PALOMA-2 trial, for AIsensitive patients, [6][7][8]37] and in combination with fulvestrant 500 mg every 28 days in the PALOMA-3 trial, for AI-resistant [11,[38][39][40]. Ribociclib was investigated in combination with letrozole 2.5 mg/day in the MONALEESA-2 trial for AI-sensitive post-menopausal women [12,15,16,[41][42][43][44], in combination with tamoxifene or NSAI (with goserelin to suppress ovarian function) in premenopausal AI-sensitive women in the MONALEESA-7 trial [16,45], and in combination with fulvestrant both for AI-sensitive and AIresistant patients in the MONALEESA-3 trial [17]. Finally, abemaciclib was used in combination with anastrozole 1 mg/day or letrozole 2.5 mg/day, as per physician choice, for AI-sensitive patients in the MONARCH-3 trial, [19,20] and in combination with fulvestrant 500 mg every 28 days for AI-resistant patients in the MONARCH-2 trial [18,24].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%